Shupihui: Conquista de la Selva. | Alternativas: Federaciones Indigenas. | Zona Franca y Desarrollo Regional. - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1981)
De octubre a diciembre de 1981, surgió la publicación de la revista Shupihui volumen 06, numero 20 bajo la dirección del Padre Joaquin Garcia, con el objetivo de aclarar temas sobre la conquista de la amazonia, federaciones indigenas, como la zona franca y desarrollo regional. La revista se comprometió a ser una voz orientadora, esclarecedora y divulgadora en la amazonia peruana para los diversos temas existentes de actualidad y analisis de latinoamerica y el mundo.

From October to December 1981, the magazine Shupihui volume 06, number 20 was published under the direction of Father Joaquin Garcia, with the objective of clarifying topics about the conquest of the Amazon, indigenous federations, such as the free trade zone and regional development. The magazine is committed to be a guiding voice, enlightening and disseminating in the Peruvian Amazon for the various existing issues of current affairs and analysis of Latin America and the world.
Shupihui: Conquest of the Jungle. | Alternatives: Indigenous Federations. | Free Trade Zone and Regional Development.
Keywords: Iquitos (Peru)--periodicals Peru--general periodicals Peru--periodicals Iquitos (Perú)--revistas Perú--revistas generales Perú--revistas